Implementasi Rumah Kemas Pada Rantai Pasok Baby Buncis Kualitas Ekspor - Fauzan Romadlon; Isnaini Nurisusilawati (Jurnal Ilmiah Teknik Industri, 2019)
This study aims to discover at the effects of the implementation of pack house in the supply chain of green bean from various aspects. The background of this study is the phenomenon of uneven distribution of pack house from the Department of Agriculture. The research object is involved 100 green bean’s farmers from Magelang. The used methods are observing, surveying, and interviewing in term of logistics cost. Multiple linear regression analysis is used to predict yields based on several cost components of green bean. There are two model equations that emerge from this method. The first equation assesses the relationship between yield and total production and transportation cost. This equation has the best significance value at the total cost of agricultural inputs. The second equation assesses the relationship between yield and the breakdown of the agricultural inputs. While the effects of pack house are to set as a non-agricultural operational hub that connect among stakeholders in green bean supply chain.